The Proportion of Regulatory T Cells in Patients with Systemic Lupus Erythematosus: A Meta-Analysis - Sheng-Xiao Zhang; Xiao-Wen Ma; Yu-Feng Li; Na-Ling Lai; Ze-Hao Huang; Kai Fan; Cai-Hong Wang; Xiao-Feng Li (Journal of Immunology Research)
Background. Accumulating evidence indicates that a deficiency in or dysfunction of regulatory T cells (Tregs) is involved in the pathogenesis of systemic lupus erythematosus (SLE). As different markers have been used to identify Tregs, recent studies on the proportions of Tregs in SLE patients have generated controversial results. To clarify the status of Tregs in such patients, we determined the proportions of Tregs present during development of the disease, with special consideration of controversial cellular markers. Methods. We identified studies reporting the proportions of Tregs in SLE patients by searching relevant databases through March 2018. Using the PRISMA guidelines, we performed a random effects meta-analysis of the frequencies of Tregs defined in different ways. Inconsistency was evaluated using the I-squared index (I2), and publication bias was assessed by examining funnel plot asymmetry using the Begger and Egger tests. Results. Forty-four studies involving 2779 participants were included in the meta-analysis. No significant difference in the proportions of Tregs was evident between 1772 patients and 1007 controls [−0.191, (−0.552, 0.362), p=0.613, I2=95.7%]. We next conducted subanalyses based on individual definitions of Tregs. When the Treg definition included “FOXP3-positive” cells, the proportions did not differ between SLE patients and controls [−0.042, (−0.548, 0.632), p=0.889, I2=96.6%]; this was the case when Tregs were defined as either “CD25low/−FOXP3+” or “CD25high/+FOXP3+” cells. SLE patients had lower proportions of Tregs that were “single CD25-positive” [−1.428, (−1.982, −0.873), p<0.001, I2=93.4%] and “CD127-negative” [−1.093, (−2.002, −0.183), p=0.018, I2=92.6%] compared to controls. Tregs defined as “CD25bright,” “CD25bright/highCD127low/−,” and “CD25highCD127low/−FOXP3+” did not differ in proportion between SLE patients and controls. Conclusions. The Treg proportions varied by the cellular identification method used. The proportions of Tregs that were accurately identified and functionally validated fell among patients with SLE. Stricter definitions of Tregs are necessary when evaluating the status of such patients.